Peningkatan Keaktifan dan Hasil Belajar Siswa melalui Media Papan Mata Uang pada Materi Nilai dan Kesetaraan Mata Uang di Kelas 2 MI Miftahul Ulum - Irmawati Aprilia; Yulina Fadilah (AS-SABIQUN, 2023)
This study aims to increase the activity and learning outcomes of grade 2 students at MI Miftahul Ulum Kropak Bantaran Probolinggo, especially in the subject matter of values and currency equality using currency board media. Because students are easily fooled about the value and change when transacting. This study used the Classroom Action Research method or Classroom Action Research, abbreviated as CAR. The subjects in this study were 35 students of grade 2 MI Miftahul Ulum consisting of 18 female students and 17 male students. In this study consisted of 2 cycles. Data collection techniques used in this study are: observation, interviews, tests, and documentation. The results showed that there was an increase in teacher activity from the beginning of cycle 1 from 72.5% to 85.0% in cycle 2, as well as student activity which increased from the beginning of cycle 1 from 73.75% to 87.50% in cycle 2. Likewise, student learning outcomes also experienced an increase from the pre-cycle which obtained an average of 64.14 with a completeness percentage of 42.85%, and increased in cycle 1 with an average of 74.57 with a completeness percentage of 74.14%, and at the end of cycle 2 an average of 84.85 was obtained with a completeness percentage of 88.57%. Thus it can be concluded that using currency board media can increase the activity and learning outcomes of Mathematics in the subject matter of values and currency equality in class II MI MIFTAHUL ULUM Kropak Bantaran Probolinggo students in the 2022/2023 academic year